A winter by the sea - Klassen, Julie, 1964- (Klassen, Julie, 1964- On Devonshire shores, 2023)
"When the Duke and Duchess of Kent rent a nearby house for the winter, the Summers sisters are called upon to host three of the royal couple's male staff in their seaside cottage, but soon they realize they've invited mysterious secrets into their home. With the arrival of their new guests, the sisters face surprising romance and unexpected danger."--